2023
DOI: 10.1172/jci161507
|View full text |Cite
|
Sign up to set email alerts
|

A TRPV4-dependent neuroimmune axis in the spinal cord promotes neuropathic pain

Abstract: Microglia, resident macrophages of the central nervous system (CNS), are essential to brain development, homeostasis, and disease. Microglial activation and proliferation are hallmarks of many CNS diseases including neuropathic pain. However, molecular mechanisms that govern the spinal neuro-immune axis in the setting of neuropathic pain remain incompletely understood. Here we show that genetic ablation or pharmacological blockade of transient receptor potential vanilloid type 4 (TRPV4) markedly attenuated neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…We further tested whether genetic ablation of Hk2 in microglia affects neuropathic pain. Studies have shown that tamoxifen induction 4 weeks before the experiment allow the retention of Cre‐mediated effects in long‐living microglia, but not in peripheral monocytes and macrophages with rapid turnover (Figure 3a) (Ajami et al, 2007; Hu et al, 2023; Muller et al, 2010; Parkhurst et al, 2013; Peng et al, 2016). We used the same strategy to achieve selective ablation of Hk2 in microglia by TAM induction in Cx3cr1 creER/+ :: Hk2 fl/fl mice, 4 weeks before the SNI surgery.…”
Section: Resultsmentioning
confidence: 99%
“…We further tested whether genetic ablation of Hk2 in microglia affects neuropathic pain. Studies have shown that tamoxifen induction 4 weeks before the experiment allow the retention of Cre‐mediated effects in long‐living microglia, but not in peripheral monocytes and macrophages with rapid turnover (Figure 3a) (Ajami et al, 2007; Hu et al, 2023; Muller et al, 2010; Parkhurst et al, 2013; Peng et al, 2016). We used the same strategy to achieve selective ablation of Hk2 in microglia by TAM induction in Cx3cr1 creER/+ :: Hk2 fl/fl mice, 4 weeks before the SNI surgery.…”
Section: Resultsmentioning
confidence: 99%
“…154 TRPV4 expression in spinal resident microglia is increased in the mouse model of SNI, which transforms peripheral nerve injury into central sensitization and neuropathic pain through releasing lipocalin-2. 155…”
Section: Central Inflammation Contributes To the Pathogenesis Of Chro...mentioning
confidence: 99%
“…154 TRPV4 expression in spinal resident microglia is increased in the mouse model of SNI, which transforms peripheral nerve injury into central sensitization and neuropathic pain through releasing lipocalin-2. 155 Astrocytes are more abundant (approximately 2-4 times) compared to microglia, and play crucial effects on controlling the extracellular microenvironment, repairing the imbalance of potassium, glutamate, and water homeostasis under normal physiological conditions. 156,157 Astrocytes are activated in various pathological conditions and convert to reactive states (also termed "astrogliosis") characterized by obvious morphological changes, a significant increase of GFAP, and a significant cellular proliferation, which is considered to be coupled with a loss of homeostatic functions of astrocytes.…”
Section: Pain Modulation By Central Glial Cellsmentioning
confidence: 99%
“…11,44 These studies provide valuable insights into the contribution of LCN2 in pain signaling pathways and potential as a therapeutic target. 11 However, the effect of LCN2 on development of morphine tolerance and hyperalgesia remain unclear. Nonetheless, our immunofluorescence staining results conclusively illustrate that LCN2 is predominantly expressed in astrocytes subsequent to the development of morphine tolerance, with minimal to no expression observed in microglia.…”
Section: Pain Medicinementioning
confidence: 99%